Perceptions of The Primary Stakeholders on Fisheries Information Services in Kerala State: An Evaluation Study - M JAYAPRADEEP AND R RAMAN NAIR* (LIBRARY HERALD, 2014)
Fishery sector occupies a crucial place in the socio-economic development of the State of Kerala. Though Kerala boasts of the highest quality of life, the State’s fishing community continues to lag behind-socially and economically. Fisheries is a specialized field wherein the information, an ingredient and a problem-solving tool, is a key factor for transformation of the sector. Speedy and effective exploitation of the knowledge acquired in the sector has to be applied in education, research, development and extension activities for the sustainable development of the sector. The State has adequate information resources but they are not optimally utilized by the primary stakeholders of the sector due to inadequate ICT based service systems, LIS professionalism and proper understanding of the community’s information needs. An assessment of the user perceptions on resources, services and needs of the sector shall entail for the improvement of the services and resources key to their needs and shall offer the opportunity to provide the right resource at the right time in right ways. An information system exclusive to the fisheries shall only be able to consolidate, integrate, and deliver the results in a cohesive, cooperative, resource sharing and network mode.